Measurement instruments to evaluate diaper dermatitis in children: Systematic review of measurement properties - Sibylle Reick; Marion Burckhardt; Rebecca Palm; Jan Kottner (Wiley, 2023)
Abstract Aim The aim of this study was to summarize and evaluate the empirical evidence on the measurement properties of diaper dermatitis (DD) measurement instruments in children. Design Systematic review. Methods MEDLINE, CINAHL and EMBASE were systematically searched until 14 June 2021. Citation searching was conducted in Scopus. The risk of bias, the reported measurement properties and the quality of evidence were evaluated using the COSMIN framework. The reporting follows the PRISMA 2020 statement. Results We identified 1200 records in the databases and 108 records during citation searching and included four studies describing three measurement instruments for DD in children and their measurement properties. We considered the content validity inconsistent for all three instruments. The study authors reported internal consistency, reliability and construct validity for one instrument. We rated the quality of evidence from very low to moderate.